Implementation of Integrated Curriculum in Developing an Interest in Memorizing Al-Qur’an Students in MTs Sulamul Huda, Siwalan, Ponorogo - Miftahul Ulum; Rahmat Yuliansyah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
The curriculum is an educational program design that contains a series of experiences given to learners to achieve a desired goal with a series of learning experiences. The curriculum has a very strategic position in the overall learning activities, which will determine the process and outcomes of student learning. Therefore, it is necessary to implement a curriculum implementation strategy in schools that are effective and efficient, especially in optimizing the quality of learning. One of the prominent activities in the Madrasah is Tahfidz Al-Qur'an. Memorizing the Qur'an is a conscious and earnest effort to remember and apply the scriptural reading of the Qur'an containing miracles, using appropriate methods and strategies. As well as what to do and what to keep in order to actually get RIDHO of Allah S.W.T. researchers want to conduct research because see the results of observations in MTs Sulamul Huda has held the program Tahfidz Al-Qur'an, will But still the low interest of pupils to memorize the Qur'an. Due to still run not long enough so not optimal in the management program Tahfidz Al-Qur'an. See the very importance of memorizing the Qur'an in adolescence, it is very important to discuss and be thorough